Migration, Urban Poverty and Underclass - "Working in the Garbage" - Hakan Acar (Social Work & Society, 2006)
With its socio-cultural and economic indicators and its location, Turkey has a contradictory social structure. At one hand, Turkey is one of the leading economies in the world. IMF (International Monetary Fund) informed that Turkey was the 21st biggest economy in 2004. It also indicated that Turkey would be the 17th biggest economy in 2006. It means Turkey will have a bigger economic power than Taiwan, Belgium or Switzerland. In contrast to its economic growth, governments of Turkey still fight for eliminating and reducing deep poverty rates. The State Statistic Institute (2004) stated that the number of poor people in Turkey has reached to 20 million in 2003. 23% of families and 37.8% of pre-school children live under poverty line. People need to find new strategies to cope and manage their lives. In this manner garbage collecting can be considered as a new employment field for the new urban poor in Turkey. Today, thousands of people and their families in Turkey have been involved in garbage collecting process as low-paid workers. This research aims to present one of the proofs of urban poverty and lack of social regulations towards the new urban poor. This study is a describing field research regarding the workers who work in city garbage in Ankara, Turkey. Research was conducted with 51 workers in 2003. Data were gathered by using a questionnaire prepared by the researchers. Researchers have used field observations and interviews as a secondary data gathering method in order to provide a rich presentation of results. At the end of the work, it is revealed that a majority of the workers in Mamak Garbage are adolescent and younger adults and have extremely low educational level. Significant numbers of the workers have immigrated to Ankara within the last 6 months from rural areas of the hinterland of Ankara. It is understood that these workers have been engaged in marginal jobs before. The garbage workers show typical characteristics that apply to members of the underclass. They have been living in poor conditions, generally employed in junk jobs for short-term periods and they continue to have little chance to develop their conditions. This can be characterized as typical poverty cycle. The workers have to work in difficult conditions such as long working hours and lower wages without social insurance.